The Effect of Leadership and Work Environment on Employee Productivity with Work Motivation as an Intervening Variable at PNM Medan Branch - Alfian Langkamane; A. Dewantoro Marsono (International Journal of Scientific Multidisciplinary Research, 2023)
The purpose of this study was to examine the the impact of leadership and the workplace environment on employee motivation and work productivity PNM Medan Branch employees. This study uses a quantitative approach with Structural Equation Modeling (SEM) using the PLS program. and IBM Statistics SPSS 26.0. The unit of analysis used is all employees of the Medan Branch of PNM. The sample consists of 135 respondents. The data collection technique was carried out using a questionnaire distributed online. The results of the study show that work motivation can mediate the influence of leadership and work environment significantly on work productivity at PNM Medan Branch